Ethical Conflicts Between Healthcare Providers and Institutional Policies - Almudaini, Abdullah Faisal; Alhajjimohammed, Mahdi Mohammed; Alanazi, Faisal Owaid; Alnasser, Osama Mohammed; Alkhateeb, Abdulmohsen Ibrahim; Arishi, Nouriyah Haider; Alkhawajah, Sajidah Hassan; Alamri, Dhafer Ali (Journal of Posthumanism, 2024)
Recently, ethical conflicts between healthcare providers and institutional policies have been encountered in various healthcare settings. These conflicts occur at different levels in healthcare teams including nurses and physicians. Multiple previous studies have reported various themes of ethical conflicts experienced by nurses and physicians due to institutional policies such as workload that can impact safety and/or quality of patient care, constraints on healthcare funding, and lack of resources. Moral distress can be the result of these conflicts; moral distress is defined as the condition that occurs when a healthcare provider experiences a conflict between what they see as the right thing to do and external obstacles, most commonly institutional policies. Moral distress is prevalent among healthcare providers, leading to significant psychological, physical, and professional consequences. However, due to the busy schedules of healthcare providers and the chaotic realm of hospitals, identifying, assessing, and resolving moral distress and conflicts between healthcare providers and institutional policies remain challenging. Thus, this review aims to discuss the current evidence investigating ethical conflicts between healthcare providers and institutional policies. Physicians identified the insufficient resources and lack or preventive focus as a source of ethical conflict with the institution. While nurses spoke about how inadequate staff-to-patient ratios and workload are major sources for ethical conflicts. Future research should prioritize institution-level interventions over individual strategies, particularly those that empower early-career professionals and promote ethically aligned practice environments.